MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI MELALUI MODEL PEMBELAJARAN INVESTIGASI KELOMPOK DENGAN MEDIA ZOOM MEETING DAN GOOGLECLASSROOM SISWA SMPN 11 JAKARTA - MASRUROH MASRUROH (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This study aims to improve students' skills in learning to write exposition texts and motivate students to get satisfactory knowledge scores. This class action research was carried out in two cycles, carried out from the month of Agustus until October 2021 in class VIII D of SMPN 11 Jakarta. Most students have not understood the material of the Exposition text. The factors that affect it include (1) lack of interest in learning Indonesian (2) Lack of communication in the learning process (3) Lack of supporting prerequisites in students. The foregoing is the result of observations that the researchers obtained from the list of Indonesian values that the researchers obtained in the material for writing class VIII D exposition texts in the 2021/2022 academic year. From this background, researchers have a problem"Can the group investigation learning model increase the activeness and learning achievement of class VIII D students for the 2021/2022 academic year on the material for writing exposition texts? The purpose of the research is to improve learning outcomes Indonesian class VIII D for the 2021/2022 academic year through a group investigation learning model by using google Classroom zoom meeting media. How to collect data by post tests and distributing questionnaires. The action plan is implemented in two cycles covering the stages of planning, implementing, observing, reflecting, and analyzing. Each cycle is held 2 times. The indicators set are the average score of students according to KKM in schools < 77, learning activity < 75%, learning completion < 75%, and absorption < 75%. From the results of the analysis obtained, namely in the precyclical student learning activity (72,5%,) in cycle I (76.55%), and in cycle II (85.83%). For absorption in the precyclical period (75.25%), Cycle I (78,8%,), Cycle II (83.72%) the increase from precyclical to Cycle I by (2.83%) and the increase from Cycle I to Cycle II by (5.64%).Based on a significant increase, the group investig ation learning model with zoom meeting media and google classroom can be applied to learning Indonesian class VIII D in the material of writing exposition The group investigation learning model can be used as one of the effective learning models, especially during a pandemic. ABSTRAKPenelitian ini bertujuan untuk meningkatkan keterampilan siswa dalam pembelajaran menulis teks eksposisi dan memotivasi siswa untuk mendapatkan nilai pengetahuan yang memuaskan. Penelitian Tindakan kelas ini dilakukan dalam dua siklus, di kelas VIII D SMPN 11 Jakarta.Sebagian besar siswa belum memahami materi teks Eksposisi. Adapun faktor yang mempengruhi diantaranya (1) kurangnya minat belajar Bahasa Indonesia (2) Kurangnya komunikasi dalam proses pembelajaran (3)Kurangnya prasyarat pendukung dalam diri siswa.Hal tersebut di atas merupakan hasil pengamatan yang peneliti peroleh dari daftar nilai Bahasa Indonesia materi menulis teks eksposisi kelas VIII D pada tahun pelajaran 2021/2022. Tujuan penelitian ini adalah untuk meningkatkan hasil belajar Bahasa Indonesia kelas VIII D tahun pelajaran 2021/2022 melalui model pembelajaran Investigasi kelompok dengan menggakan media zoom meeting dan google Classroom. Cara pengumpulan data dengan post test dan penyebaran angket. Rencana tindakan dilaksanakan dengan dua siklus mencakup tahapan perencanaan, pelaksanaan, observasi, refleksi, dan analisis. Setiap siklus dilaksanakan 2 kali pertemuan. Indikator yang ditetapkan yaitu nilai rata-rata siswa sesuai KKM di sekolah < 77 , keaktifan belajar < 75%, ketuntasan belajar < 75%, dan daya serap < 75%. Dari hasil analisis didapatkan, pada prasiklus keaktifan belajar siswa (72,5%,) pada siklus I (76,55%), dan pada siklus II (85,83%). Untuk daya serap pada masa prasiklus (75,25%), Siklus I (78,8%,), Siklus II (83,72%) kenaikan dari prasiklus ke Siklus I sebesar (2, 83%) dan kenaikan dari Siklus I ke Siklus II sebesar (5,64%). Berdasarkan kenaikan yang cukup signifikan maka model pembelajaran investigasi kelompok dengan media zoom meeting dan google classroom dapat diterapkan pada pembelajaran Bahasa Indonesia kelas VIII D pada materi menulis teks eksposisi . Model pembelajaran investigasi kelompok dapat dijadikan salah satu model pembelajaran yang efektif, khususnya pada masa pandemi.